2021
DOI: 10.3390/vaccines9101134
|View full text |Cite
|
Sign up to set email alerts
|

Reported COVID-19 Vaccination Coverage and Associated Factors among Members of Athens Medical Association: Results from a Cross-Sectional Study

Abstract: There are limited data on the prevalence and determinants of COVID-19 vaccination coverage among physicians. A cross-sectional, questionnaire-based, online study was conducted among the members of the Athens Medical Association (I.S.A.) over the period 25 February to 13 March 2021. All members of I.S.A. were invited to participate in the anonymous online survey. A structured, anonymous questionnaire was used. Overall, 1993 physicians participated in the survey. The reported vaccination coverage was 85.3%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
(42 reference statements)
6
18
2
Order By: Relevance
“…It should be underlined that in both Western and Asian countries, it has been widely reported that the positive emotion of the public towards the safety of the COVID-19 vaccine was associated with increased vaccination uptake [ 39 , 40 , 41 , 42 ]. This highlights the need for comprehensive and coordinated health promotion campaigns, to improve understanding of the importance of vaccines and efforts of healthcare providers about the COVID-19 vaccine among this population, to equip them with easily understandable information.…”
Section: Discussionmentioning
confidence: 99%
“…It should be underlined that in both Western and Asian countries, it has been widely reported that the positive emotion of the public towards the safety of the COVID-19 vaccine was associated with increased vaccination uptake [ 39 , 40 , 41 , 42 ]. This highlights the need for comprehensive and coordinated health promotion campaigns, to improve understanding of the importance of vaccines and efforts of healthcare providers about the COVID-19 vaccine among this population, to equip them with easily understandable information.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another important point is that the healthcare professionals have ethical, legal, and moral obligations to protect their patients [ 8 ]. In one research, the main reasons for not being vaccinated were a pending vaccination appointment and safety concerns [ 4 ]. Moreover, frequent social media exposure and interpersonal discussion potentially might increase the vaccination willingness [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if the vaccination rates are higher among healthcare workers when compared to general population [ 4 , 8 ], the majority is against mandatory vaccination [ 3 ]. The rates of vaccine acceptance increased with age, being highest in the over-55 group [ 3 , 6 , 7 ] and also with the fear of COVID-19 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Georgios Marinos et al [ 4 ] conducted a cross-sectional, questionnaire-based, online study, which was conducted among the members of the Athens Medical Association. The finding that participants reported high reliability of the information related to COVID-19 vaccination provided by the Greek public health authorities is an opportunity which should be broadly exploited by policymakers in order to combat vaccination hesitancy, and further improve COVID-19 vaccination uptake and coverage among physicians/health care workers and the general population.…”
mentioning
confidence: 99%